PENGARUH DAN STRATEGI KOTA BANDUNG DI SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH BANDUNG - Hadrian Gustin Urdha; Anthony Sebastiane Chandra; Eva Hany Fanida (Journal of Law and Administrative Science, 2026)
The tourism sector is a source of income that utilizes a region's tourism potential, including natural tourism, cultural tourism, culinary tourism, health tourism, religious tourism, and various other types of tourism. Knowledge of each region's tourism potential is crucial for it to become a productive source of regional income. This paper will discuss the impact of the tourism sector on regional income, particularly in Bandung. This paper is expected to provide a different perspective and address public doubts about the potential of their respective regions. Therefore, Bandung will serve as an example of how to wisely utilize tourism potential and positively impact regional income. Keywords: tourism sector, sources of income, tourism potential, regional income